Kemiskinan Struktural Terhadap Masyarakat Marginal: Studi Kasus di Pemukiman Pemulung Wilayah Bintara Jaya, Bekasi Barat (Jurnal Insan Pendidikan dan Sosial Humaniora, 2025)
Structural poverty is a complex phenomenon that occurs due to systemic inequality in economic, social and political structures, which traps marginalized groups in a cycle of poverty that is difficult to break. This research aims to analyze the impact of structural poverty on waste pickers in the Bintara Jaya slum, West Bekasi, focusing on internal and external factors that reinforce the cycle of poverty. The research method uses a descriptive qualitative approach through in-depth interviews with five waste picker informants. The results show that structural poverty in the waste picker community is influenced by limited access to education, informal work with unstable income, inadequate living conditions, and the lack of government policy intervention. Internal factors such as low levels of education and skills, as well as external factors such as social stigma and non-inclusive policies, exacerbate the condition. Despite facing severe challenges, the waste picker community still has hope to escape poverty, especially through their children's education. This research recommends the need for more holistic and inclusive policies to break the cycle of structural poverty, including improved access to education, skills training, and social protection for marginalized communities.